Hack Kampmann (1999)
Información gráfica de la ampliación de la Gliptoteca Ny Carisberg, Copenaghen, 1900.
Keywords: DINAMARCA; KØBENHAVN; COPENHAGUE; MUSEOS DE ARTE; MUSEOS; AMPLIACION; HISTORIA; KAMPMANN, HACK